Stress-Strain Compression of AA6082-T6 Aluminum Alloy at Room Temperature. (13th November 2014) - Scari, Alexandre da Silva; Pockszevnicki, Bruno Cesar; Landre Junior, Jánes; Magalhaes Junior, Pedro Americo Almeida
Abstract : Short cylindrical specimens made of AA6082-T6 aluminum alloy were studied experimentally (compression tests), analytically (normalized Cockcroft-Latham criteria—nCL), and numerically (finite element analysis—FEA). The mechanical properties were determined with the stress-strain curves by the Hollomon equation. The elastic modulus obtained experimentally differs from the real value, as expected, and it is also explained. Finite element (FE) analysis was carried out with satisfactory correlation to the experimental results, as it differs about 1, 5% from the damage analysis by the nCL concerning the experimental data obtained by compression tests.